Pengembangan Kapasitas Korban Kekerasan dalam Rumah Tangga Melalui Pendekatan Pemberdayaan Sosial Ekonomi - Dadang Hikmah Purnama; Komarudin (Pubmedia Social Sciences and Humanities, 2025)
Domestic violence (DV) has wide-ranging impacts on the psychological, social, and economic aspects of victims, hindering their ability to achieve independence. This study aims to examine strategies for empowering DV victims in Palembang City using participatory and qualitative methods. The research process consists of three main stages: capacity assessment, strategy planning, and implementation. The first stage involves exploring victims' conditions through interviews, focus group discussions (FGDs), and field observations to identify their challenges and needs. The second stage focuses on designing a community-based empowerment strategy through skills training, access to business capital, and psychosocial assistance. The third stage involves implementing the program through entrepreneurship training, mentoring, and strengthening social networks, engaging various stakeholders, including the government, social organizations, and the private sector. The findings indicate that a participatory approach can enhance victims' social and economic capacities, promote independence, and strengthen community support. Cross-sector collaboration is a key factor in creating a sustainable empowerment model. This study contributes to the enhancement of policies and practices for protecting DV victims through strategies based on real needs.